The Effect of Course Shutouts on Community College Students: Evidence from Waitlist Cutoffs - Silvia Robles; Max Gross; Robert W. Fairlie (Institute of Labor Economics (IZA), 2020)
One frequently cited yet understudied channel through which funding levels impact college students is course availability—colleges are often forced to respond to budgetary pressure by reducing course offerings. We provide the first causal evidence on this mechanism at a community college, using administrative course registration data and a novel research design that exploits discontinuities in course admissions created by waitlists. Community colleges enroll about half of U.S. undergraduates and over half of minority students in public colleges. The impacts of course availability in this setting may be especially salient relative to four-year colleges due to open admissions policies, binding class size constraints, and a heavy reliance on state funding. Across a range of bandwidths, we find that students stuck on a waitlist and shut out of a course section were 22 to 28 percent more likely to take zero courses that term relative to a baseline of about 10 percent. Shutouts also increased transfer rates to nearby, but potentially less-desirable two-year colleges. These results offer some evidence that course availability can disrupt community college students' educational trajectories.
Keywords: I23; 330; community college; waitlist; course shutout; course scarcity; transfers